344 Drivers of Adverse 30-Day Outcomes for Pediatric Spine Tumor Surgery Patients: A Nationwide Analysis. (April 2023) - Tang, Oliver Young; Chen, Jia-Shu; Groves, Mari L.; Shao, Belinda; Ganga, Arjun; Svokos, Konstantina; Klinge, Petra Margarete; Zadnik Sullivan, Patricia Leigh
Abstract : INTRODUCTION: Spine tumors in children are an uncommon clinical entity. Drivers of reoperation and readmission following surgery for this pathology are poorly characterized. METHODS: We conducted a retrospective cohort analysis of all spine tumor surgery cases in the National Surgical Quality Improvement Program-Pediatrics database from 2012-2020, using diagnosis and Current Procedural Terminology codes. The primary outcome was a composite of 30-day mortality, reoperation, readmission, and non-home discharge disposition. Stepwise regression with bidirectional elimination via the Akaike Information Criterion was used to identify predictors of adverse 30-day outcomes. 25 candidate variables were assessed, including tumor characteristics, patient demographics, preoperative comorbidities, operative details, and postoperative complications. RESULTS: The analytic cohort included 728 pediatric patients undergoing spine tumor surgery. Patients predominantly had intradural intramedullary tumors (79.3%). Average age was 7.7 years and 54% were male. 86.5% were discharged to home. 30-day mortality rate was 0.4%. 48 patients (6.6%) required reoperation, with the most common reasons being infection (n = 14), repair of cerebrospinal fluid leak (n = 8), shunt placement (n = 8), and tumor recurrence (n = 6). 39 patients (5.4%) underwent readmission within 30 days, primarily for surgical site infection (n = 11), nervous system complication (n = 8), or wound dehiscence (n = 7). Stepwise regression identified predictors of adverse 30-day outcomes including emergent surgery (OR = 2.64, P = 0.014), operative time (OR = 1.03 per +10 minutes, P < 0.001), length of stay (OR = 1.03 per +1 day, P = 0.035), surgical site infection or dehiscence (OR = 5.26, P < 0.001), nervous system complications (OR = 10.31, P = 0.009), and non-surgical site infections (OR = 27.95, P < 0.001). When mortality, reoperation, and readmission were analyzed in aggregate, emergent surgery and postoperative complications remained as significant predictors. CONCLUSIONS: 30-day adverse events following pediatric spine tumor surgery were predominantly driven by emergent surgery, prolonged operative or hospitalization time, and postoperative complications.